Developing a Cryptosystem for Multimedia Data - Abdelsalam Abdelhamid ALMARIMI; Ibrahim Ali ALMERHAG; Farag ABDULAZIZ (International Journal of Applied Methods in Electronics and Computers, 2015)
The multimedia information is not secure in the wireless systems compared to that of wired systems. So, there is a necessity to encrypt the information and transmit over wireless medium and then receive the encrypted information from the wireless medium to recover the original information using a decryption method. In this paper, we propose a new method of cryptographic algorithm by combining both the symmetric key mono alphabetic shift ciphering and the RSA (Rivest, Shamir, and Adleman) algorithm which can be more applicable to the future generation of wireless systems. We have developed an algorithm for generating the RSA secret keys. The simulation is implemented in MATLAB. The security performance is studied for multimedia data files such as text, audio and image. Since, RSA is based on modular exponentiation, our experimental results show that the proposed algorithm is very efficient and secure for practical implementation as a multimedia cryptosystem.